Effects of Increasing Concentrations of Maize-Expressed Non-Starch Carbohydrase Enzyme on Broiler Growth Performance and Ileal Nutrient Digestibility - Jasek , A.; Li, X.; Xu, H.; Raab, R.M.; Broomhead, J.N.; Lee, J.T. (International Journal of Poultry Science, 2018)
Background and Objectives: An experiment (phase 1) was conducted to evaluate the retained activity of a maize-derived, recombinant carbohydrase enzyme (AC1) when exposed to heat during the pelleting process and homogeneity when mixed into mash diet. A second experiment (phase 2) was conducted to evaluate the effects of increasing AC1 concentrations on male broiler growth performance and ileal nutrient digestibility. Materials and Methods: A total of 728 broilers were randomly assigned to seven dietary treatments with each treatment consisting of 13 replicates with eight Cobb 500 male broilers. The experimental design included a positive control (PC), a reduced energy negative control (NC, comprising the PC less 132 kcal kg–1) diet and five additional treatments with increasing dose of AC1 (5, 50, 100, 250 and 500 U glucanase kg–1) added to the NC diet. Birds were fed a starter ration for the duration of the study (16 d). Average body weight (BW), mortality adjusted feed conversion ratio (FCR) and feed consumption (FC) were determined on 16 d of age. At the conclusion of the experiment, all birds from each replicate pen were necropsied and ileal contents pooled within replicate to determine ileal digestibility of energy (IDE) and nitrogen (IDN). Results: In Phase 1, the recovery of ß-glucanase activity in the pellets (in relation to mash feed) were 111, 83 and 82% when pelleted at 80, 85 and 90°C, respectively. The coefficient of variation of glucanase recovered when AC1 was mixed into feed and was less than 10%. In Phase 2, the inclusion of AC1 at 100 and 250 U glucanase kg–1 increased (p<0.01) BW compared to both the PC and NC fed broilers. This elevation in BW was related to an increase (p<0.01) in FC. As expected, reducing energy in the NC diet decreased (p<0.01) IDE value of the feed as compared to the PC diet. The addition of AC1 to supply ≥100 U glucanase kg–1 increased (p<0.01) IDE compared to the NC diet and restored IDE equivalent (p>0.05) to the PC diet. Regression analysis confirmed linear and quadratic increases in IDE and IDN with the addition of AC1. Conclusion: These data demonstrate the thermal stability of maize-derived, recombinant AC1 and that increasing levels positively influences nutrient digestibility leading to significant improvements in broiler performance.